Simulation-based trajectory tracking coordination of intelligent vehicle with explicit model prediction. (7th January 2021) - Xu, Xingyuan; Xie, Liyang; Zhang, Yin
In this paper a novel approach to trajectory tracking problem of intelligent vehicle is presented. A model-based optimisation algorithm for steering systems with multiple physical constraints is designed. A simplified linear vehicle model is designed in order to improve its real-time ability. Moreover, an offline solving method based on explicit model predictive control (EMPC) is presented to improve the computation speed. The simulation results show the offline solving method has the same tracking performance compared with the online solving problem by YALMIP toolbox. The computation speed is significantly increased.